Development of a law library consortium in Metro Manila - Jaafar, Tadz Majal Ayesha V.; Apolinario, Rhea Rowena U.; Aguirre, Vyva Victoria M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
It is an established fact that no library is complete and can give everything to its clients. The reasons behind this include the continuously rising costs of library resources and services, information explosion, and advances in technology, among others. To ensure that the information needs of the clients are satisfied, consortia are formed, wherein the libraries can share resources and services. In the Philippines, consortia and networks have been proven to be effective in addressing the above-mentioned concerns. No consortium, however, was formed for law libraries. There are only informal arrangements among law librarians. Thus, this study proposes a model for a law library consortium in Metro Manila and a Memorandum of Agreement.
Before coming up with a model, several factors were examined. This study described the current status of law libraries in Metro Manila-their practices, the services that they offer, specialize in and share with other libraries, and the resources available in each library. This study also sought to find out the attitude of law librarians and the institutions' administrators towards sharing resources with other institutions. Based on the findings on the above-mentioned factors and some literature reviewed, a model for a law library consortium was formulated.
The search techniques used in the study were the survey method and interview. Survey questionnaires were distributed to the clients of the law libraries in order to describe their information needs. The librarians were also given another set of survey questionnaires to identify their practices, the materials that they have in their libraries, the services that they offer and their attitude towards resource sharing. On the other hand, interviews were conducted with the administrators of the institutions to know their attitude towards resource sharing.
The findings of this study were: (1) clients have various ways of seeking information, but have almost the same information needs; (2) the information that they are looking for an individuals and the information that their institutions require from them are almost the same, as well as their preferred characteristics of information; (3) the most used sources of information are textbooks, case digests and online/electronic resources, most clients consult foreign materials, and most clients prefer print materials; (4) the most sought information are laws, executive orders, proclamations, decisions, references and news; (5) most of the clients spend 0-4 hours in seeking information; (6) most clients are satisfied with their research but admit that not everything they need could be found in the library; (7) most clients think that collaboration with other institutions is necessary; (8) the different law libraries have almost the same practices; (9) various sources of legal information and services are available in the different law libraries and the librarians are willing to share them; (10) most librarians are willing to collaborate with other institutions, and; (11) most administrators gave an affirmative response regarding the idea of establishing a law library consortium, as long as equal sharing will be done and confidentiality of other records will be kept.
The model created for the law library consortium, based on the results of the study, will have its own staff with certain qualifications, funding from membership fees, fees from the services and grants, joint ownership of assets and infrastructure, incorporated and recognized as a legal entity, governed by a board of directors formed for the consortium, and has committees handling different services and activities which work hand-in-hand with one another. It is concluded that the law library is considered as a vital part of the institution. A law library consortium will be helpful for the clients, librarians and the institutions in providing adequate service. Collaboration is also a good idea for law libraries in Metro Manila since the libraries have various collections and services. It will also be easier for libraries to collaborate with one another because most of them have almost the same practices, and most of the librarians and administrators have an affirmative response towards the establishment of a law library consortium.
The following recommendations were made: (1) the law librarians should keep track of the latest developments in librarianship and law; (2) a periodic and objective assessment of the collection and services should be done; (3) the practices and services that they offer; (5) the librarians must try to be open to the concept of resource sharing; (6) the administrators must be informed of the advantages and disadvantages of the consortium, and; (7) the establishment of the law library consortium should be done as soon as possible, using the model established based on the results of this study as a guide.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Library cooperation -- Philippines -- Manila Metropolitan Area; Law libraries -- Philippines -- Manila Metropolitan Area